Pengaruh Perubahan Penjualan,Capital Intensity Ratio, Debt to Asset Ratio, dan Current Ratio terhadap Cost Stickiness dalam Perusahaan di Bursa Efek Indonesia - Nelmida Nelmida; Stephen O. H. Siregar (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
This paper attempted to understand the cost behavior known as cost stickiness in Indonesian companies, and the influence of capital intensity ratio, debt to asset ratio and current ratio to cost stickiness. This understanding is expected to shed light into cost behavior during business downturn. The research utilized regression model developed by Anderson, Banker and Janakiraman, to analyze behavior of Sales, General and Adminisitrative cost when there is a decrease of sales.This research used data of companies listed in the Indonesian Stock Exchange as sample for the population of the Indonesian companies. The research did not find evidence of cost stickiness, but discovered indication of relationship between capital intensity ratio, debt to asset ratio and current ratio with cost behavior during sales downturn.